Influencing factors on entrepreneurial intention: Intermediary role of achievement motivation, risk-taking propensity and innovativeness - Thuc, Nguyen Ngoc (Nurture, 2024)
Purpose: This study examines the mediating relationships of achievement motivation, risk-taking propensity and innovativeness as well as the influencing factors of self-efficacy, family support, peer influence and institutional support on the entrepreneurial intentions of young individuals in Vietnam. Design/Methodology/Approach: The research questionnaire was distributed to major universities in Hanoi, Ho Chi Minh City, Da Nang, significant economic and political centres in Vietnam, and numerous leading universities. The author analyzed the impact of independent and mediating variables on the dependent variable, entrepreneurial intention using the PLS-SEM software and the 425 valid responses collected. Findings: The research results indicate the positive influence of self-efficacy, family support and peer support on entrepreneurial intention through the impact of mediating variables, including achievement motivation, risk-taking propensity and innovativeness. Conclusion: This study has highlighted the positive influence of self-efficacy, family support, peer support and institutional support on entrepreneurial intention through the mediating effects of achievement motivation, risk-taking propensity and innovativeness. Research Limitations/Implications: Several managerial recommendations are proposed to boost the Vietnamese’ future entrepreneurial startup rate. Practical Implications: This study supplements and refines the model of factors influencing entrepreneurial intention by examining the influence of mediating variables, namely achievement motivation, risk-taking propensity and innovativeness on entrepreneurial intention. Contribution to the Literature: The study's limitations encompass convenience sampling which may affect representativeness and generalizability. Additionally, surveying only students may not fully represent young individuals in Vietnam.